Lo que la investigación sabe acerca del uso de manipulativos virtuales en el aprendizaje de la matemática - Matus Zúñiga, Claudia (2010)
Technology has revolutionized many aspects of life. Information and communication technologies, in particular, have also promised to transform education, enabling students´ access to new learning environments and enriching their school experiences. In recent years, online technologies have allowed and made possible to emerge a new generation of manipulatives, called virtual manipulatives (VM). These VM are very flexible web-based applications to be used as important tools for teaching and learning mathematics more effectively. This article presents virtual manipulatives describing their features, advantages, and restrictions as they have been encountered in different recent field studies. In addition, the article discusses some of the reasons why virtual manipulatives are important resources for current teaching and learning mathematics.